Synthesis and antioxidant activity of zinc(II) phthalocyanine tetranitroxide. (15th March 2021) - Korkut, Sibel Eken; Ahmetali, Erem; Bilgi, Mesut; Karataş, Özgül; Yerli, Yusuf; Peksel, Ayşegül; Şener, M. Kasım
Graphical abstract: Zinc(II) phthalocyanine bearing four TEMPO fragments at the non-peripheral positions of the macrocycle was prepared and its magneto structural and antioxidant properties were studied. The results show that zinc(II) phthalocyanine derivative has a powerful antioxidant activity at various antioxidant systems in vitro. Highlights: ZnPc with stable free radical TEMPO moieties was synthesized. The in vitro antioxidant activity of the ZnPc derivative was studied. ZnPc has strong DPPH radical scavenging and β-carotene bleaching activities. Abstract: Zinc(II) phthalocyanine ( np -TEMPO-ZnPc ) bearing four TEMPO fragments at the non-peripheral positions of the macrocycle was prepared through the cyclotetramerization of phthalonitrile derivative 3-TEMPO-Pht . Characterization of tetraradical was performed by electron paramagnetic resonance (EPR) at room temperature. A characteristic triplet was observed ( g = 2.00715, hyperfine coupling constant of 15.73 G ) in the EPR spectrum of np -TEMPO-ZnPc measured in chloroform. The np -TEMPO-ZnPc was also investigated for in vitro antioxidant activities. Antioxidant properties were determined for its free radical scavenging effect, reducing power, β-carotene bleaching and total antioxidant capacity assays. The results demonstrated that np -TEMPO-ZnPc has strong DPPH radical scavenging and β-carotene bleaching activities even more than the standard antioxidant BHT. Especially, the compound exhibited similar radical scavenging effect at low concentrations when compared with BHT.